2021
DOI: 10.1158/1055-9965.epi-21-0733
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Healthcare Providers' Recommendation of HPV Vaccination for U.S. Adolescents: A Systematic Review

Abstract: Infrequent provider recommendations continue to be a key barrier to human papillomavirus (HPV) vaccination, including among adolescents at higher risk for future HPV cancers. To inform future interventions, we sought to characterize disparities in health care providers' HPV vaccine recommendation for U.S. adolescents. We systematically reviewed studies published in 2012–2019 that assessed provider HPV vaccine recommendations for adolescents aged 9–17. Following Preferred Reporting Items for Systematic Reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Our findings suggest disproportionate rates of recommendations among patients who are black, Hispanic, male or reside in rural areas. Similar to our study, a systematic review by Kong et al found higher rates of provider recommendation among women, white patients, higher income populations, and urban dwellers 41. Providers may be reluctant to recommend the HPV vaccine for adolescent patients due to concerns of discussing sexual activity or decreased perception of susceptibility of HPV 119.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings suggest disproportionate rates of recommendations among patients who are black, Hispanic, male or reside in rural areas. Similar to our study, a systematic review by Kong et al found higher rates of provider recommendation among women, white patients, higher income populations, and urban dwellers 41. Providers may be reluctant to recommend the HPV vaccine for adolescent patients due to concerns of discussing sexual activity or decreased perception of susceptibility of HPV 119.…”
Section: Discussionsupporting
confidence: 85%
“…Ninety-seven included studies assessed inequities between sex or gender and HPV (online supplemental table 2). Patients identifying as female largely had increased rates of HPV and HPV vaccine-related knowledge, HPV vaccination and provider recommendations compared with men 22 38–41. Patients identifying as male had higher prevalence of HPV infections,23 25 28 29 higher rates of oropharyngeal squamous cell carcinoma,42–45 and worse outcomes related to anal squamous cell carcinoma 37 46 47.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing implementation efforts on clinician recommendations is warranted as the clinician’s recommendation has been shown repeatedly to be associated with positive vaccine outcomes for boys and girls at series initiation and completion [ 7 , 8 ]. However, the percentage of parents who report receiving a clinician recommendation for HPV vaccine ranges from 12 to 76% [ 9 ]. In one study among parents who did receive a recommendation, only about half stated their clinicians expressed urgency of vaccinating during the visit, indicated the vaccine was important, or mentioned that the vaccine prevents cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 This may contribute to providers' inconsistent practices with recommending the vaccine, such as the tendency to initiate vaccination more often in older rather than younger adolescents. 3 Another major reason for not completing the HPV vaccination in adolescence is vaccine refusal, with 30% of parents in 1 survey reporting that they refused or delayed an HPV vaccine dose offered to their children. 4 Among adolescents, continuity of health care may further influence HPV vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%